BUSINESS PERFORMANCE: BALANCED SCORECARD ANALYSIS FOR INDONESIA PUBLISHING HOUSE (IPH) - Victor Sinaga; Judith Sinaga (Jurnal Ekonomis, 2020)
The study aimed to analyze the business performance of Indonesia Publishing House (IPH). Descriptive method was used to explain the business performance using balanced scorecard (BSC) model. There were 30 respondents who participated in this study. The findings showed that the four BSC perspectives (financial, customer, internal business process, and learning and growth) attained the level of good. IPH business performance needs some improvements to achieve the highest level of performance.